THE RELATIONSHIP BETWEEN GADGET ADDICTION AND INTEREST IN STUDYING AND SLEEP QUALITY IN SCHOOL CHILDREN - Ananditha, Aries Chandra; Priyantini, Diah; Novelia, Ranty Dwi (Universitas Airlangga, 2024)
Introduction: Excessive use of gadgets in children can lead to addiction and the bad impact can influence students' interest in studying and sleep quality because students will experience dependence and explore more of the other applications of gadgets. This research aims to analyze the relationship between gadget addiction interest in learning and sleep quality in school children. Methods: The research method is quantitative and uses a cross-sectional approach. The sample of this study was 83 children in 6th-grade elementary school at SD Muhammadiyah 21. Gadget addiction was measured with a modified questionnaire consisting of 30 favorable items, which were then altered and tried out into 21 questions, consisting of 14 favorable items and 7 unfavorable items with a Cronbach's alpha reliability test result of 0.880. Interest in learning is measured with a questionnaire consisting of 4 answer items and sleep quality is measured with a sleep quality questionnaire (SQQ). Research data analysis used the Spearman rho correlation test. Results: There is a relationship between gadget addiction and interest in learning (p=0.000; (r) = 0.902) and there is a relationship between gadget addiction and sleep quality (p=0.000; (r) = 0.843).Conclusions: So, it can be concluded that there is a significant relationship between gadget addiction and students' interest in learning and sleep quality. So, teachers should have a good relationship with students' parents to control the intensity of students' gadget addiction and foster students' motivation to learn and get enough sleep.